Parental educational homogamy and under-five mortality in sub-Saharan Africa: Clarifying the association’s intricacy (2020)
Worldwide, under-five mortality (U5M) rate is highest in sub-Saharan Africa (SSA). There exists a gap in knowledge on the pathway through which Parental Educational Homogamy (PEH) influences U5M in SSA. In this study, we tested the research hypothesis’ PEH is not associated with under-five children’s survival probability in SSA. Demographic and health survey datasets for 21 SSA countries were analyzed. Cross sectional design and multi-stage cluster sampling technique were used for sample selection in each of the countries under investigation. The dependent variable was the survival status of a newborn to age 59 months while the main independent variable was PEH generated from information on wife’s and husband’s level of education. Data were analyzed using Chi-square test, Cox-proportional hazard model and Brass-adjusted model (α=0.05). Under-five mortality rate ranges from 56/1,000 live born in South Africa to 190/1,000 live born in Sierra-Leone. Across countries, U5M rate was higher among the children of parents with at most primary education than that of parents who had at least secondary education. This pattern of U5M rate was also observed for children of parents where husbands were more educated than their wives. Maternal age at birth, sex of the child, toilet facility, type of cooking fuel, tetanus injection during pregnancy, and birth weight were significantly associated with U5M in 14, 11, 8, 7, 11, 14 and 20 countries respectively. A significant relationship was established between PEH and U5M in 11 of the 21 studied countries but was identified as a predictor of U5M in Congo Democratic Republic, Gambia and Zimbabwe. Parental educational homogamy exhibits a pattern of relationship with U5M in SSA. Ensuring that individuals particularly women have at least secondary education before child bearing will facilitate an U5M reduction in SSA.